MENGUJI KONSEP PERTANGGUNGJAWABAN PIDANA KORPORASI - Adriano - (Universitas Airlangga, 2013)
An entity, either a legal or the non legal “entity’’ which all were discussed in the same outline of corporate crime responsibility. It was often, though, in several laws aside from the Penal Code of Indonesia (KUHP), both in Criminal Law and Administrative Law with criminal sanction,that corporate is defined as a collection of organized people and or wealth, either as a legal or the non legal entity. The definitions in those laws are really different from those of law experts, especially those of criminal law who basically identify corporate as a legal entity, however the same is not true for those of the non legal entity. Such differences of the legal and non legal entities would bring their own legal consequences, therefore they could not and would not be treated the same referring to corporate criminal responsibility.Keywords: corporate criminal responsibility, legal entity, non legal entity.